Anonim şirketlerde pay sahibinin bilgi alma hakkı - Birinci, Betül (My University, 2019)
Anonim şirketlerde pay sahibinin sahip olduğu en önemli haklardan birisi bilgi alma ve inceleme hakkıdır. Bilgi alma ve inceleme hakkı ile pay sahibi ortaklığa ilişkin bilgiye erişir ve ortak sıfatını devam ettirip ettirmeyeceğine karar verir. Bu kapsamda çalışmamızın birinci bölümünde bilgi alma ve inceleme hakkı kavramı, tanımı, kapsamı ve hukuki niteliği ele alınmıştır. İkinci bölümde bilgi alma ve inceleme hakkı sahibi ile yükümlüsü incelenmiştir. Üçüncü bölümde bilgi alma ve inceleme hakkının kullanılması ve şirket tarafından reddi halleri incelenmiştir. Son olarak dördüncü bölümde bilgi alma ve inceleme hakkının ihlali halinde ve pay sahibinin istediği bilgiye erişememesi durumunda başvurabileceği hukuki yollar ele alınmıştır.

One of the most important rights of the shareholder in joint stock companies is the right to demand and review information. With the right to demand and review information, The shareholder reaches the information regarding to the partnership and decides whether to maintain the title of partner or not. Within this scope; the definition, the extent and the concept of right to demand information and examine, and its legal characteristic have been addressed in the first section of our work. In the second section, the right to demand information and examine and the obligant have been inspected.In the third section, the usage of the right to receive and review information and the types of rejections by the company have been analysed. Finally, in the fourth section, the legal actions ' that the shareholder can take in case of the violation of the right to demand and investigate information; moreover in the event that the shareholder is not able to reach the information requested' have been discussed.
Keywords: Civil law; Commercial law; Hukuk; inceleme hakkı; Law; Medeni hukuk; Pay sahibinin bilgi alma hakkı; right to examination; Shareholder’s right to information; Ticaret hukuku